How do you solve #x^2 - 6x + 6 = 0# using the quadratic formula?

Answer 1

#x_1 = 4.73# (3sf) #x_2 = 1.27# (3sf)

The quadratic formula is: #(-b +- sqrt(b^2 - 4ac))/(2a)#, Therefore the first step is to identify #a,b# & #c#. We need to ensure that the equation is #=0# and in this case that is true.
Then we are able to obtain the values to substitute into the formula; the general quadratic formula layout is #ax^2 + bx +c# therefore we look at your equation: #x^2 - 6x + 6#. The value of #a# has to be #1# since #x^2# is multiplied by #1#. Then #b = -6#, maintaining the negative is essential to the calculation (the sign will also stay with the value that is next in the equation). Then #c = 6#.
We now substitute #a= 1#, #b=-6# and #c= 6# into the quadratic formula.
#x = (-b +- sqrt(b^2 - 4ac))/(2a)# #= (-(-6) +- sqrt((-6)^2 - 4(1)(6)))/(2(1))#

After the values have been changed in the equation, we must first solve the square root's interior.

#x = (-(-6) +- sqrt(12))/(2(1))#
Since the value under the root (discriminant) is positive we know that there will be two real solutions for #x#.
Separate the two #x# values so that we solve for the positive root first.
#x_1 = (-(-6) + sqrt(12))/(2(1))# = #4.73# (3 sf)
Now solve the second #x# value by using the negative root.
#x_2 = (-(-6) - sqrt(12))/(2(1))# = #1.27# (3 sf)
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

Sure, to solve the equation (x^2 - 6x + 6 = 0) using the quadratic formula, you would follow these steps:

  1. Identify the coefficients (a), (b), and (c) in the equation (ax^2 + bx + c = 0).

    • In this case, (a = 1), (b = -6), and (c = 6).
  2. Substitute these values into the quadratic formula: (x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}).

  3. Plug in the values for (a), (b), and (c):

    • (x = \frac{-(-6) \pm \sqrt{(-6)^2 - 4(1)(6)}}{2(1)}).
  4. Simplify the equation:

    • (x = \frac{6 \pm \sqrt{36 - 24}}{2}),
    • (x = \frac{6 \pm \sqrt{12}}{2}),
    • (x = \frac{6 \pm 2\sqrt{3}}{2}).
  5. Split into two solutions:

    • (x_1 = \frac{6 + 2\sqrt{3}}{2} = 3 + \sqrt{3}),
    • (x_2 = \frac{6 - 2\sqrt{3}}{2} = 3 - \sqrt{3}).

So, the solutions to the equation (x^2 - 6x + 6 = 0) are (x = 3 + \sqrt{3}) and (x = 3 - \sqrt{3}).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7